Torture behind bars : role of the police force in India - Aston, Joshua Nathan (New Delhi : Oxford University Press, 2020)
This volume critically examines the role and accountability of the police in India and lays emphasis on the human rights of citizens referring to international instruments and the guidelines of the National Human Rights Commission for the prevention of custodial violence and protection of victims and their rights.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 1, 2020).
Keywords: Police -- India; Police brutality -- India; Prisoners -- Violence against -- India; True Crime; Social services & welfare, criminology